Effectiveness of Lanterns Application on Making Lanterns Skills Improvement From Sewing Yarn for Deaf Children - Yolla Denara; Mega Iswari (EDUTEC : Journal of Education And Technology, 2020)
This study discusses the skills to make lanterns from sewing yarn for deaf children. This research is experimental research. The purpose of this study is to prove the effective lanterns application used making lanterns skills improvement from sewing yarn for deaf children. This type of research is an experimental method in the form of pre-experimental with the type of one group pretest-posttest design. The subjects of this study were 5 deaf children in SLB Negeri (deaf children state) 2 Padang. This study consists of several stages, namely the first stage (pretest) to determine the initial conditions of the ability to make lanterns from sewing yarn, the second stage is given (treatment) using the lantern application, then the third stage is the last test to find out how far the results of the treatment that have been given (post-test) are processed and compared using the Wilcoxon Rank Task test. The results of research data obtained an average of pretest are 31.80 while for post-test there is an increase that is to 85.80. Data were processed using a Wilcoxon test, obtained the value of task rank between pretest and posttest 2,032 with Asymp. Sig (2-tailed) 0.042. The probability value obtained from the analysis test is compared with the predetermined probability that is ? = 0.05. The alternative hypothesis is accepted because the probability <of the established probability is 0.042 <0.05. So it is proven that the use of the lantern application is effective in improving the skills of making lanterns from sewing yarn for deaf children